Women and Inequality: An Analysis of Social Structures in The Lives of Female Agricultural Laborers in Batipuah Baruah Village - Siska Elasta Putri; Muhammad Hizbi Islami; Satri Widya Nengsih; Mami Nofrianti (Alfuad: Jurnal Sosial Keagamaan, 2025)
This study analyzes the relationship between social structure and women's decision to work as farm laborers in Batipuah Baruah Village. In rural communities that rely heavily on the agricultural sector, women often face complex challenges in choosing their professions. This research employs a qualitative approach with a descriptive design, involving in-depth interviews with women who work as farm laborers. The results indicate that although economic needs are the primary factor, women's decisions to enter the agricultural sector are also influenced by social structures, such as gender inequality, limited access to resources, social norms related to family roles, and geographical constraints that restrict employment opportunities. Additionally, women farm laborers in Batipuah Baruah Village demonstrate remarkable resilience and creativity in addressing various challenges, such as low wages and heavy workloads. This study concludes that social structures not only shape women's economic choices but also reinforce patterns of gender inequality in the workplace. Thus, changes in social structures are necessary to provide women with greater access to resources and equal employment opportunities.